Keanekaragaman Tumbuhan Ritual dalam Tradisi Megengan : Kajian Etnobotani di Kampung Budaya Polowijen Kota Malang - Windi Rahmawati; Nabila Khikmaturrosyida; Cahya Silvika Ramadhina; Fahrul Ghani Muhaimin; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
Megengan is a ritual of gratitude and communal prayer practiced by the Javanese community, utilizing various plant species as the main components in the cultural procession to welcome the holy month of Ramadan. This study aims to identify, analyze, and document the plant species used, their utilization, symbolic meanings, as well as conservation efforts within the Megengan tradition in Kampung Budaya Polowijen. This research employed a qualitative approach with a descriptive-exploratory method. Data were collected through interviews, observations, and documentation involving traditional leaders and practitioners of the Megengan tradition. Key informants were determined using purposive sampling, which was then expanded through snowball sampling to obtain additional sources of information. Data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that there are 12 plant species from 11 families utilized in the Megengan ritual procession, with plant parts used including flowers, leaves, fruits, seeds, and rhizomes. These plants serve both practical functions and philosophical meanings as spiritual and social symbols. Conservation efforts are reflected in the sources of the plants, which are mostly obtained from community cultivation. The conservation status of the identified species is largely categorized as not evaluated (50%), indicating that these species have not yet been scientifically assessed by official conservation institutions, thus further research is needed to support the preservation of biocultural knowledge. These findings highlight the role of the Megengan tradition in preserving ethnobotanical knowledge and maintaining harmony between the community and the environment.